Natural pseurotins inhibit proliferation and inflammatory responses through the inactivation of STAT signaling pathways in macrophages - Vasicek, Ondrej; Rubanova, Daniela; Chytkova, Barbora; Kubala, Lukas (Food and chemical toxicology, 2020)
BACKGROUND: Natural pseurotins, secondary metabolites of fungi, commonly produced by various species such as Aspergillus flavus with suggested significant biological effects. However, little is known about effects of pseurotins on immune system functions. METHODS: Effects of pseurotin A and D on proliferation and viability of macrophage RAW 264.7 cells were evaluated together with mitochondrial respiration and glycolysis. Macrophage response to lipopolysaccharide was analyzed based on determination of nitric oxide (NO) production, expression of inducible NO synthase (iNOS), interleukin 6 (IL-6) and tumor necrosis factor production. Activation of selected signaling pathways, particularly STAT and MAPK, as well as expression of cyclins were determined. RESULTS: Natural pseurotins A and D in concentrations of up to 50 μM significantly inhibit proliferation of RAW 264.7 macrophages which was not complemented by induction of cell toxicity. The inhibition of cell proliferation was accompanied by downregulation of expression of cyclins and mitochondrial respiration via inhibition of particularly STAT3 phosphorylation. Both pseurotins significantly inhibited production of NO, expression of iNOS and IL-6 production. CONCLUSION: Our results advance the current mechanistic understanding of the pseurotin-induced inhibition of proliferation, metabolic respiration and functional responses in macrophages by linking the effect to JAK/STAT signaling pathway.
Keywords: Macrophage; signální transdukce; Immunity; Nitric oxide; cykliny; Inflammation; mitochondrie; Cyclins; mediátory zánětu; transkripční faktor STAT3; Lipopolysaccharides; zánět; Natural pseurotin; Signal Transduction; Mice; Cell Proliferation; Pyrrolidinones; Cytokines; Inflammation Mediators; pyrrolidinony; RAW 264.7 buňky; Macrophages; STAT; zvířata; lipopolysacharidy; STAT3 Transcription Factor; myši; makrofágy; proliferace buněk; Mitochondria; RAW 264.7 Cells; Animals